Paternal Postpartum Depression and Its Relationship With Maternal Postpartum Depression - Mahin Kamalifard; Somayeh Bayati Payan; Samira Panahi; Shirin Hasanpoor; Jalil Babapour Kheiroddin (Journal of Holistic Nursing and Midwifery)
Introduction: Evidence shows that some men suffer from Postpartum Depression (PPD), and that the adverse effects of this unknown phenomenon affect them and their family. Objective: The purpose of this study was to determine paternal PPD and its relationship with some factors, especially maternal PPD. Materials and Methods: This cross-sectional study was performed on 205 couples who were selected using a random cluster sampling in seven health centers affiliated to the Shahid Beheshti University of Medical Sciences six to 12 weeks after childbirth. Data was collected from fathers using the Edinburgh Postnatal Depression Scale (EPDS) and a demographic questionnaire. The Edinburgh questionnaire was also used for the mothers. Data analysis was performed using descriptive statistics and the Pearson correlation as well as the Chi-square and linear regression. Results: A total of 11.7% of the fathers had depression symptoms. There was a significant and direct correlation between the paternal and maternal PPD scores (r=0.29, P=0.001). Among the sociodemographic and fertility factors, there was a significant relationship only between a family s livelihood situation, the number of abortions and the number of pregnancies with the parental depression scores (P=0.05). In the regression analysis, maternal PPD (ß=0.22) and the family s livelihood situation (ß=0.44) predicted paternal depression (P=0.001). This model totally explained about 30% of the changes in paternal PPD (R2=0.298). Conclusion: Considering the significant frequency of depression in fathers and the role of maternal depression as well as the family s livelihood situation, it is recommended that evaluation should be carried out on paternal PPD and its risk factors in order to prevent and treat it in a timely manner